The Relationship Between Level of Knowledge and Healthy Behaviors with the Risk of Coronary Heart Disease in Teachers at SDN 106 Aek Galoga - Susanti, Nofi; Jasmine, Savina Talitha; Ramadani, Selvia; Matondang, Tria Syafira (PROMOTOR, 2024)
Coronary artery disease (CHD) is a condition caused by problems with the coronary arteries which cause narrowing and blockage, which can disrupt the body's energy transfer process and cause an imbalance between oxygen demand and oxygen supply. This research aims to determine the relationship between knowledge and Healthy Behaviors on Coronary Heart Disease Risk Factors. This research method uses correlative analysis and a cross sectional approach. This research describes the relationship between a person's knowledge and lifestyle and the risk of coronary heart disease. The sample in this study consisted of 20 adults who were teachers at SDN 106 Aek Galoga. The selected subjects were interviewed using a research questionnaire. After conducting research, it can be concluded that 4 people (20.0%) had a good level of knowledge, 13 (65.0%) had a good level of knowledge, and 3 people (15.0%) had a poor level of knowledge. The results of the chi-square test show that there is a significant relationship between the level of knowledge of the risk factors for Coronary Heart Disease with a p value of: 0.001. Based on the data we obtained from 20 respondents from SDN 106 Aek Galoga, it can be concluded that there is a relationship between knowledge and Healthy Behaviors and risk factors for Coronary Heart Disease.